An Analysis of Essay Writing Errors among English-Major Freshmen at Thu Dau Mot University - Thanh Thai Nguyen (English Education and Applied Linguistics Journal (EEAL Journal), 2026)
This study investigates the common essay writing errors made by English-majored freshmen at Thu Dau Mot University. The study aims to identify the major types of errors in students’ essays and examine the possible sources of those errors. Adopting a descriptive corpus-based error analysis design, the study analyzed 60 English essays written by first-year English-majored students. The essays were collected through a controlled writing task and examined using Corder’s (1967) framework of error analysis. The identified errors were classified into thirteen categories and analyzed quantitatively in terms of frequency and percentage, with qualitative interpretation used to explain possible causes. The findings revealed a total of 1,530 errors, with an average of 25.5 errors per essay. The most frequent error types were word form (23.99%), word choice (21.31%), and spelling (8.43%), followed by organization, verb tense, punctuation, and missing words. The findings suggest that students’ writing difficulties stem mainly from limited vocabulary, insufficient grammatical knowledge, intralingual overgeneralization, and mother tongue interference. The study highlights that freshmen’s essay writing problems are not limited to sentence-level grammar, but also extend to text organization and coherence. It is therefore recommended that writing instruction should address both linguistic accuracy and essay development skills in order to improve students’ writing performance more effectively.